I Met Lucky People: The Story of the Romani Gypsies. By Yaron Matras. London: Allen Lane, Penguin Books, 2014, 276 pp.; ISBN 978-1-846-14481-3. - Friedman, Victor A. (Social Inclusion, 2015)
This is a book review of I met lucky people: The story of the Romani Gypsies, by Yaron Matras. The work is oriented for a general reading public, but it can be highly recommended for academics and policy makers as well.